Deferred use of bevacizumab for recurrent glioblastoma is not associated with diminished efficacy. Issue 6 (13th March 2014) - Piccioni, David E.; Selfridge, Julia; Mody, Reema R.; Chowdhury, Reshmi; Li, Sichen; Lalezari, Shadi; Wawrzynski, James; Quan, Jennifer; Zurayk, Mira; Chou, Arthur P.; Sanchez, Desiree E.; Liau, Linda M.; et al.
Abstract: Background: The optimal timing to initiate bevacizumab (BV) therapy for recurrent glioblastoma (GBM) is currently unclear. To address this issue, we examined progression-free survival (PFS) and survival time (ST) in a large retrospective cohort of GBM patients treated with BV at different recurrences. Methods: We identified 468 primary GBM patients who underwent biopsy or surgery followed by radiation therapy and temozolomide (RT/TMZ), and then received BV. PFS and ST were compared between patients stratified by the recurrence that BV was initiated (upfront, first recurrence, second recurrence, or 3+ recurrences). We also examined the effect on PFS and ST of the addition of chemotherapy to BV. In a larger cohort of GBM patients, we determined overall treatment continuation rates at each recurrence and identified variables predictive of inability to continue treatment. Results: BV PFS was similar for all 3 recurrence groups (median, 4.1 months). There were no differences in BV ST (median, 9.8 months). The addition of chemotherapy to BV improved PFS but not ST. Analysis of treatment continuation rates indicated that the number of patients unable to undergo further treatments is modest, and that patients unable to tolerate BV delay can be identified by age ≥60 years and low extent of resection. Conclusions: Deferred use of bevacizumab is not associated with diminished efficacy. Analysis of treatment continuation rates identified patients who may be unable to delay BV therapy. Our findings suggest that there is a fixed survival after BV initiation and that delayed BV treatment is preferable for most patients.